Analysis of Herb Composition in the Putroe Aloeh Tourism Area, Jeumpa District, Southwest Aceh - Miftahul Munawwarah; Djufri Djufri; Wardiah Wardiah; Safrida Safrida; Muhibbuddin Muhibbuddin (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2023)
Abstrack The existence of plants in an area or area will have a positive impact on the balance of the ecosystem. Herbaceous plants play an important role in the annual nutrient cycle, namely the herb litter that is returned to the soil contains high nutrients and plays a role in adding soil organic matter so that it can prevent erosion. The purpose of this study was to determine the composition of medicinal plants in the Putroe Aloeh Tourism Area, Jeumpa District, Southwest Aceh District. The method used in this study is the observation method by determining stations using purposive sampling technique and plot placement using the square method subjectively, where at each station there are 10 plots measuring 2m x 2m. Parameters observed were the number of species and the number of individuals of each species. The research data were analyzed descriptively. Based on the research results, 50 types of herbs were found consisting of 26 families, and the dominating families were Asteraceae (20%), Rubiaceae (10%), and Araceae (8%).Keywords: Herbs, Compositon, Tourism Area Abstrak Keberadaan tumbuhan di suatu wilayah atau kaawasan dapat berdampak positif terhadap keadaan dinamis pada ekosistem. Tumbuhan herba sangat berperan terhadap putaran waktu hara tahunan, yaitu serasah herba yang dipulangkan ke tanah memuat unsur hara yang tinggi dan mempunyai peran pada penambahan bahan organik tanah sehingga bisa berfungsi sebagai pencegahan erosi. Tujuan dari penelitian ini adalah untuk mengetahui komposisi tumbuhan herba di Kawasan Wisata Putroe Aloeh Kecamatan Jeumpa Kabupaten Aceh Barat Daya. Metode yang digunakan dalam penelitian ini yakni metode observasi dengan menentukan stasiun menggunakan teknik purposive sampling dan penempatan plot menggunakan metode kuadrat secara subyektif, dimana pada setiap stasiun terdapat 10 plot yang berukuran 2m x 2m. Parameter yang diamati adalah jumlah spesies dan jumlah individu masing-masing spesies. Data penelitian dianalisis secara deskriptif. Berdasarkan hasil penelitian ditemukan 50 jenis herba yang terdiri dari 26 familia, dan familia yang mendominasi adalah Asteraceae (20%), Rubiaceae (10%), dan Araceae (8%).Kata Kunci: Herba, Komposisi, Kawasan Wisata.